[18F]FDG-PET-CT compared with CT for persistent or recurrent neutropenic fever in high-risk patients (PIPPIN): a multicentre, open-label, phase 3, randomised, controlled trial. Issue 8 (August 2022) - Douglas, Abby; Thursky, Karin; Spelman, Timothy; Szer, Jeff; Bajel, Ashish; Harrison, Simon; Tio, Shio Yen; Bupha-Intr, Olivia; Tew, Michelle; Worth, Leon; Teh, Benjamin; Chee, Lynette; et al.
Summary: Background: Management of neutropenic fever in high-risk haematology patients is challenging; there are often few localising clinical features, and diagnostic tests have poor sensitivity and specificity. We aimed to compare how [ 18 F]flurodeoxyglucose ([ 18 F]FDG)-PET-CT scans and conventional CT scans affected the guidance of antimicrobial management and the outcomes of patients with persistent or recurrent neutropenic fever. Methods: We did a multicentre, open-label, phase 3, randomised, controlled trial in two tertiary referral hospitals in Australia. We recruited adults aged 18 years or older who were receiving conditioning chemotherapy for haematopoietic stem-cell transplantation or chemotherapy for acute leukaemia and had persistent (>72 h) or recurrent (new fever beyond 72 h of initial onset interspersed with >48 h defervescence) neutropenic fever. Exclusion criteria were pregnancy, allergy to iodinated contrast, or estimated glomerular filtration rate of less than 30 mL/min. Patients were randomly assigned by computer-generated randomisation chart (1:1) to [ 18 F]FDG-PET-CT or conventional CT. Masking was not possible because of the nature of the investigation. Scans were done within 3 days of random assignment. The primary endpoint was a composite of starting, stopping, or changing the spectrum (broadening or narrowing) of antimicrobial therapy—referred to here as antimicrobial rationalisation—within 96 h of the assigned scan, analysed per protocol. This trial is registered with clinicaltrials.gov, NCT03429387, and is complete. Findings: Between Jan 8, 2018, and July 23, 2020, we assessed 316 patients for eligibility. 169 patients were excluded and 147 patients were randomly assigned to either [ 18 F]FDG-PET-CT (n=73) or CT (n=74). Nine patients did not receive a scan per protocol, and two participants in each group were excluded for repeat entry into the study. 65 patients received [ 18 F]FDG-PET-CT (38 [58%] male; 53 [82%] White) and 69 patients received CT (50 [72%] male; 58 [84%] White) per protocol. Median follow up was 6 months (IQR 6–6). Antimicrobial rationalisation occurred in 53 (82%) of 65 patients in the [ 18 F]FDG-PET-CT group and 45 (65%) of 69 patients in the CT group (OR 2·36, 95% CI 1·06–5·24; p=0·033). The most frequent component of antimicrobial rationalisation was narrowing spectrum of therapy, in 28 (43%) of 65 patients in the [ 18 F]FDG-PET-CT group compared with 17 (25%) of 69 patients in the CT group (OR 2·31, 95% CI 1·11–4·83; p=0·024). Interpretation: [ 18 F]FDG-PET-CT was associated with more frequent antimicrobial rationalisation than conventional CT. [ 18 F]FDG-PET-CT can support decision making regarding antimicrobial cessation or de-escalation and should be considered in the management of patients with haematological diseases and persistent or recurrent high-risk neutropenic fever after chemotherapy or transplant conditioning. Funding: National Health and Medical Research Council Centre of Research Excellence (APP1116876), Melbourne Health foundation, Gilead Research Fellowship grants supported this study.